Effect of water acidity on the growth performance, survival, and hematology condition of the barramundi fish Lates calcarifer (Bloch, 1790) fingerling - Mustika Marzah Fitriana; Nur Fadli; Zainal Abidin Muchlisin (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Global warming is caused by increased carbon emissions into the atmosphere resulting from burning oil, gas, and other fossil fuels. Subsequently, the carbon gas enters the waters through a diffusion process facilitated by the concentration of gases in the air, which is higher than in the waters. The outcome of this process is a decrease in water acidity, leading to a lower pH, which can disrupt the life of aquatic biotas. Therefore, this study aims to analyze the effect of decreasing of pH on the growth, survival, and physiological conditions of barramundi (Lates calcarifer). To achieve this objective, seven pH levels were tested, namely pH of 7.24 (control), pH 6.74, pH 6.24, pH 5.74, pH 5.24, pH 4.74, and pH 4.24. Every treatment was performed with four replications, and the fish was reared for 30 days in the respective tested pH. The reared madia is sea water with a salinity of 22 ppt. The experiment was conducted in the laboratory of fish breeding Faculty of Marine and Fisheries, Universitas Syiah. The results showed that a decreasing in pH had a significant effect on the growth performance and hematological condition of barramundi (P0.05), but its had no significant effect on survival (P0.05). The experimental fish could survive at pH 4.24, but their growth and hematological conditions were disrupted below 6.24. Therefore, it was concluded that the lower threshold value of pH for barramundi was 6.24.Keywords:Global warmingOcean aciditypHFisheries productionPhysiological disturbance